2006
DOI: 10.1007/s00192-006-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

Weak VLPP and MUCP correlation and their relationship with objective and subjective measures of severity of urinary incontinence

Abstract: The aims of the present study were to find the correlation between Valsalva leak-point pressure (VLPP) and cough leak-point pressure (CLPP) and to determine whether the water perfusion maximum urethral closure pressure (MUCP) correlates with VLPP. Seventy-nine women with previously untreated stress urinary incontinence were recruited to participate in a clinical study. Their mean age was 56.4 years, mean BMI was 27.8, and mean parity was 1.9. The mean values of VLPP and CLPP were 50.4 and 52.9 cm H(2)O, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Abdominal leak point pressure is often reduced in patients with SUI, and if it is ≤60 cmH 2 O, then suspect urethral sphincter deficiency . If the Valsalva method is used to increase the intra‐abdominal pressure, it is called Valsalva leak point pressure; if cough is used, it is called cough leak point pressure …”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal leak point pressure is often reduced in patients with SUI, and if it is ≤60 cmH 2 O, then suspect urethral sphincter deficiency . If the Valsalva method is used to increase the intra‐abdominal pressure, it is called Valsalva leak point pressure; if cough is used, it is called cough leak point pressure …”
Section: Diagnosismentioning
confidence: 99%
“…75 If the Valsalva method is used to increase the intra-abdominal pressure, it is called Valsalva leak point pressure; if cough is used, it is called cough leak point pressure. 76,77 Furthermore, pressure flow studies are useful for evaluating voiding disorder pathology; however, currently, there are no defined diagnostic criteria for female lower urinary tract obstruction. 78 -80…”
Section: Urodynamic Study (Uds)mentioning
confidence: 99%
“…No single parameter correlated very highly with either the diagnosis of ISD or even consistently with severity [3]. Subsequent authors have corroborated this, showing that no significant association has been demonstrated between pad test, bladder diary, QOL, and MUCP values [13,14,30]. Bump et al suggested that no single factor be considered absolutely to establish the diagnosis of ISD, and only the combination of urodynamic measurements, patient history, and clinical severity should be used to guide management [3].…”
Section: Correlation With Symptom Severitymentioning
confidence: 99%
“…A later study examined 79 women who underwent both abdominal leak point pressure measurement and urethral pressure profilometry; all had urodynamic stress urinary incontinence without previous surgery and were planned to undergo insertion of mid-urethral tape (TVT). [26] Cutoff values of 60 cmH 2 O for abdominal leak point pressure and 30 cmH 2 O for maximum urethral closure pressure were used to categorize the women. No statistical association between abdominal leak point pressure and maximum urethral closure pressure was found; suggesting they are measuring different pathophysiological events.…”
Section: Resultsmentioning
confidence: 99%